Litchi chinensis: nutritional, functional, and nutraceutical properties - Guillermo Castillo-Olvera; José Sandoval-Cortes; Juan A. Ascacio-Valdes; Jorge E. Wong-Paz; Olga B. Álvarez-Pérez; María L. FloresLópez; Cristóbal N. Aguilar (Food Production, Processing and Nutrition)
Abstract Litchi chinensis is a tree in the Sapindaceae family. It is originally from China but grows in countries with tropical or subtropical climates. It has great commercial value because of its juiciness and fresh pulp. It is a rich source of nutrients and bioactive compounds (procyanidin type A and B, epicatechin, rutin, and quercetin). The compounds present in litchi have been reported to confer functional properties, such as antioxidant, anticancer, antimicrobial, and nutraceutical properties, and are believed to have the potential to develop new functional foods or products. This review summarizes the botanical characteristics and cultivation methods of litchis. Its nutritional composition has also been described, which includes a macronutrient and micronutrient profile; its functional properties, such as antioxidant, anti-inflammatory, and anticancer potential; and the relationship between bioactive compounds and their medicinal potential. Despite their beneficial qualities, litchi fruits face significant challenges in terms of conservation. Rapid browning of the pericarp is a major problem resulting in considerable product loss. Therefore, producers must develop sustainable strategies for the conservation and valorization of fruits and their byproducts. Therefore, it is necessary to look for innovative solutions that take advantage of the bioactive properties of litchi, which can be used to develop innovative pharmaceutical, food, or cosmetic products. Graphical Abstract